Analysis, design, and control of standalone PV based boost DC-AC converter - Nayak, Jnanaranjan; Kumar, Sunil; Sahu, Pradeep Kumar; Jena, Satyaranjan (International Journal of Applied Power Engineering (IJAPE), 2024)
This paper presents a new control scheme for a boost DC–AC converter which is used for solar power applications. The proposed DC-AC converter configuration can produce an AC voltage level across the output or load side greater than input DC voltage based on the operating duty cycle. Generally, the conventional DC-AC converter or voltage source inverter (VSI) generates AC voltage which is less than input DC voltage. Maintaining a constant voltage across the load with improved dynamic performance is challenging for anyone for the solar photovoltaic (PV) system. A dual-loop sliding mode control is proposed for the boost VSI to address the above issues. The proposed controller has robust in nature against the wide fluctuation in the plant or load parameters. The design, analysis and control of the boost DC-AC converter are briefly discussed in this paper. This topology can be broadly used in solar powered uninterruptible power supply (UPS) where boosting operation is essential for low voltage solar PV system. This topology eliminates the DC boosting power processing stage which leads an improved efficiency of the overall system. The MATLAB/Simulink results are presented to highlight the above issues.